Restorative Justice Peredaran Rokok Ilegal Dampaknya terhadap Penerimaan Cukai Negara Indonesia - M Ichwan Labib; Ardiansyah Ardiansyah (LPPM Iblam School of Law, 2026)
Illegal cigarette circulation is a serious threat to Indonesia's excise tax revenue, which contributes more than 90% of total national excise income. This study uses a normative juridical approach to examine two interconnected issues: first, the implementation of law enforcement against illegal cigarette distribution based on restorative justice principles; and second, optimization efforts to mitigate the potential excise revenue losses caused by illegal cigarette circulation. The study finds that restorative justice cannot be fully applied in illegal cigarette cases because the offense inherently involves state financial loss, a condition incompatible with the prerequisites of restorative proceedings. Administratively, however, fines remain applicable under Article 14 of Law Number 39 of 2007 on Excise. On the optimization side, the government must pursue a multi-pronged strategy encompassing proportional tariff reform, strengthened law enforcement capacity by the Directorate General of Customs and Excise (DJBC), inter-agency coordination, adoption of Track and Trace technology and artificial intelligence, and active community participation through public education and whistleblower incentive programs